Paepalanthus (Eriocaulaceae) without scapes and spathes, a survey with the description of a new species - Andrade, Maria José Gomes De; Trovó, Marcelo; Rocha, Lamarck; Giulietti, Ana Maria (Phytotaxa, 2022)
Eriocaulaceae are mainly characterized by their unisexual flowers arranged in capituliform inflorescences at the apex of scapes surrounded by closed spathes. The lack of the scapes and spathes is a rare condition in the family, restricted to a small number of species in Eriocaulon, Paepalanthus, and Syngonanthus. In this manuscript we explore the species of Paepalanthus lacking spathes and scapes based on morphological and molecular data (ITS, trnL-trnF, and psbA-trnH). The specimens with dimerous flowers form a monophyletic group represented by the only two species of P. subg. Thelxinoë. The accessions with trimerous flowers cluster with species of the polyphyletic P. ser. Leptocephali. As expected, the ancestral character reconstruction indicates that the loss of scapes and spathes occurred at least twice in Paepalanthus, but probably occurred four to five times in the family. Based on molecular data, SEM images, and morphological analysis, most of the specimens lacking scapes were assigned to previously described species with the exception of the trimerous-flowered specimens treated here as a new species, P. paganuccii. Besides the full treatment for this new species, we provide an annotated checklist for all Paepalanthus species without scapes, with nomenclatural novelties, a distribution map, illustrations, photos, and a comparative table.